Belief in a Just World and Emotional Intelligence in Subjective Well-Being of Cancer Patients. (31st May 2019) - Megías, Jesús L.; Romero, Yolanda; Ojeda, Begoña; Peña-Jurado, Inmaculada; Gutiérrez-Pastor, Pilar
Abstract: The study of coping strategies has provided valuable insights about the process of helping cancer patients adapt to their disease. However, new approaches must be explored to increase the knowledge of this adjustment. In this study, we will analyze the relationship between patients' psychological well-being and quality of life and less well-studied constructs such as the belief in a just world (BJW) and emotional intelligence (EI). Sixty-eight cancer patients (35 men, 33 women; mean age 53.5 years; range: 20–86) were asked about their personal and general BJW, EI, Perception of Quality of Life, Anxiety, and Depression. Different multiple regression analyses showed that patients' personal BJW negatively predicted their anxiety ( p < .05) and a trend to a better quality of life. In addition, patients with high scores in the Mood Repair subfactor of EI showed better quality of life ( p < .05), and those with higher Attention to Feelings exhibited more Anxiety ( p < .01) and a trend to more Depression. These results underline the need to take into consideration new factors, such as BJW and EI, in clinical interventions for cancer patients.